2011
DOI: 10.1016/j.ymgme.2011.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in membrane caveolae and BKCa channel activity in skin fibroblasts in Smith–Lemli–Opitz syndrome

Abstract: The Smith-Lemli-Opitz syndrome (SLOS) is an inherited disorder of cholesterol synthesis caused by mutations in DHCR7 which encodes the final enzyme in the cholesterol synthesis pathway. The immediate precursor to cholesterol synthesis, 7-dehydrocholesterol (7-DHC) accumulates in the plasma and cells of SLOS patients which has led to the idea that the accumulation of abnormal sterols and/or reduction in cholesterol underlies the phenotypic abnormalities of SLOS. We tested the hypothesis that 7-DHC accumulates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 67 publications
1
19
0
1
Order By: Relevance
“…The single-channel conductance of the BK Ca channel, which colocalizes with caveolin in CHOLrich membrane domains, is reduced and the voltage dependence of the open probability is right-shifted in SLOS fibroblasts [48]. The function of Na + /K + ATPase is also decreased in SLOS fibroblast [48].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The single-channel conductance of the BK Ca channel, which colocalizes with caveolin in CHOLrich membrane domains, is reduced and the voltage dependence of the open probability is right-shifted in SLOS fibroblasts [48]. The function of Na + /K + ATPase is also decreased in SLOS fibroblast [48].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, accumulation of the 7DHC in the plasma membrane can affect the physicalchemical behavior of the lipid bilayer, and also influence the function of membrane proteins by disrupting/modifying the raft structure and/or interacting directly with the proteins themselves [11,30,61]. The single-channel conductance of the BK Ca channel, which colocalizes with caveolin in CHOLrich membrane domains, is reduced and the voltage dependence of the open probability is right-shifted in SLOS fibroblasts [48]. The function of Na + /K + ATPase is also decreased in SLOS fibroblast [48].…”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol is an important component of the lipid rafts of cell membranes, it is the constituent of myelin, the precursor molecule of bile acids, steroid hormones and neurosteroids and plays an important role in the embryogenesis/morphogenesis as well [Kelley et al, 1996]. In SLO syndrome 7-DHC replaces cholesterol to a great extent in the steroland caveolin-rich membrane regions and disturbs cell signaling [Ren et al, 2011]. Very recently, it has been suggested that the neurological symptoms in SLO syndrome are associated with the oxysterols that are produced out of 7-DHC [Korade et al, 2010].…”
mentioning
confidence: 99%
“…Disruptions in cholesterol metabolism can interrupt key signaling pathways that participate in the normal maintenance of pulmonary www.intechopen.com vascular tone. Others and we have found that caveolae-dependent signaling may be involved in this process since our patient had altered expression of caveolin-1 suggesting that additional cellular alterations beyond mere changes associated with abnormal sterols in the membrane likely contribute to the pathogenesis of SLOS (Katheria, et al, 2010;Ren et al, 2011).…”
Section: Smith-lemli-opitz Syndromementioning
confidence: 59%